ANALISIS KESIAPAN KOTA PROBOLINGGO MENUJU KOTA KREATIF (STUDI PEMBANGUNAN BERKELANJUTAN DENGAN KONSEP KOTA KREATIF PMK3I) - Lailatul Fitria, Nurul Jannah (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
Regional development has potential and distinctive advantages. So that government policies in development prioritize local potential. Development with the Kemenparekraf concept called Creative Word with Self-Assessment of Creative Districts or Cities of Indonesia (PMK3I). Probolinggo City has a commitment to Creative City development with local potential orientation. Such as local resources and Pandalungan culture. The author is interested in conducting in-depth research to analyze the readiness of Probolinggo City towards a Creative City with PMK3I through research with descriptive qualitative methods. The main (primary) and supporting (secondary) data sources were obtained using interview techniques, direct observation, and documentation. The location focused on Probolinggo City and was conducted in January and February 2023. Data analysis was carried out by collecting data, simplifying or classifying data, presenting data, and drawing conclusions. In addition, the analysis applied the concept of creative city parameters. The implementation of research to ensure data validity requires technical test. So that it is known that the Probolinggo City Government is implementing a strategy towards a creative city. Indicators to measure or determine that the creative city have been fulfilled are the creative economy, creative groups, and creative environment, although there are still variables that are not perfect. Fulfillment of creative city indicators requires the involvement and interrelation of parties in building a Creative City. The parties involved in the development of the creative city consist of five actors, namely the government, academics, business people, media, and communities. The five factors together apply the principles of a creative city. This shows the readiness of Probolinggo City towards a creative city by looking at creative economic readiness, creative group readiness, and creative environmental readiness. The goal is that this development is not just a formality development in accordance with City Branding but also for sustainability.